THE USE OF “TEACHER RACES GAME” IN TEACHING SPEAKING DESCRIPTIVE TEXTTO THE SEVENTH GRADE STUDENTS OFSMP MUHAMMADIYAH 2 TAMAN (RETAIN, 2013)
AbstrakBahasa Inggris merupakan salah satu ketrampilan yang harus bisa dikuasai oleh siswa, namun masihbanyak siswa yang malu dalam mengungkapkan idenya dalam berbicara bahasa inggris. Denganmemberikan kesempatan lebih untuk menyampaikan ide, para siswa diharapkan untuk bisa memotivasidiri untuk mampu berbicara dalam Bahasa Inggris. Salah satu usaha yang bisa dilakukan oleh guru adalahmenerapkan permainan di dalam kelas. Permainan merupakan salah satu tehnik yang dapat memotivasisiswa dalam proses pembelajaran di dalam kelas. Permainan Teacher races game merupakan sebuahpermainan yang dapat mengaktifkan kemampuan berbicara siswa. Item bahasa yang diaplikasikan dalampermainan ini menggunakan salah satu jenis teks yaitu teks deskriptif. Penelitian ini menggunakan jenispenelitian deskriptif kualitatif. Subyek dalam penelitian ini adalah siswa kelas VII A di SMPMuhammadiyah 2 Taman. Instrumen dalam penelitian ini adalah tabel observasi dan rubrik ketrampilanberbicara. Data dalam penelitian ini adalah hasil observasi dan deskripsi nilai ketrampilan berbicara siswayang dikumpulkan selama proses pembelajaran di dalam kelas. Setelah observasi dilakukan, penelitimendeskripsikan hasil observasi dan nilai ketrampilan berbicara siswa.Kata Kunci: Permainan Teacher Races, ketrampilan berbicara, teks deskriptifAbstractSpeaking is one of the skills that have to be mastered by student in learning English. But, there are manystudents that still afraid to make mistake and feel depressed in speaking activity. By giving moreopportunities to speak, students are asked to encourage themselves to speak in English. One of theteacher’s efforts is implementing the game since games can motivate students in learning process.Teacher races game is a kind of simulation game that can activate students’ speaking ability. Thelanguage applied in this game uses the descriptive text. This research is a descriptive qualitative research.The subject is VII-A class of SMP Muhammdiyah 2 Taman . The researcher uses observation checklistand students‟ performance score from rubric of speaking proficiency as the instrument. The data areobtained from the observation during the implementation of Teacher Races game and students ‟performance score. After being observed, the researcher described two findings. the observation resultfrom the implementation of Teacher Races game that the teacher had done and the students‟ speakingability are addressed.Keywords: Teacher Races game, speaking, descriptive textINTRODUCTIONBackground of the StudyEnglish has to be taught in all grades of junior highschool, senior high school and even in elementary school.(decree no. 060Fu/1993 in Dellyana, 2008:1). Besidesthat, based on the competency based curriculum (2006:2)the teaching of English is emphasized on the four languageskills: reading, listening, speaking, and writingSpeaking has an important role for EnglishForeign Learner (EFL) in the real language learning.Speaking is one of the skills that have to be mastered bystudent in learning English. Many experts definespeaking in different ways. Lado (1961: 240-241) statesthat speaking ability is someone‟s ability to transfer theirknowledge and to express their idea in realcommunication by selecting correct words andsystematized idea. It means that speaking ability is theability to express oneself in one live situation in preciseEjournal Unesa. Volume 01 Nomor 01 Tahun 2013, 1 - 11words, or the ability to converse, or to express a sequenceof ideas fluently.Teaching speaking in junior high schoolstudents is not easy as turning a hand, because Seventhgrade students include in teens or young adult that “anage of transition, confusion, self-consciousness,growing, and changing bodies and minds” (Brown2001:106), so it is between childhood and adulthood.The thing that should be considered is that children havetheir own characteristics. Some of the teachers feel thatthe students are reluctant and get difficulty in speaking.They feel that it is very difficult to arrange the class inthe good atmosphere. On the other hand there are manystudents that still afraid to make mistake and feeldepressed in speaking activity.Alongside those statements, English teachershould be able to encourage and facilitate the students inorder to speak English as much as possible. The one ofappropriate technique to build the students‟ motivationin learning speaking English is by using game whilethey are learning. Games can motivate the students inlearning the language. They will be encouraged in thelearning process if they are given the cheerful technique.In line with the benefit of game has beenstated, in this study, the game is used to teach speakingdescriptive text to the seventh graders. And it is calledteacher races game. Teacher races game is one of thegood ways to teach speaking and to improve thestudent‟s speaking ability. In the teacher‟s races game,the students have chance to deliver their idea to theirteacher. Smith (2008) states although in practicing thisgame the pupils will need extra energy to run more andmore to get the right answer. It means, at the same timewhile they do drilling they memorize the lesson bythemselves. So it is believed by doing this game, thestudents‟ speaking ability will be better that before. AsSmith (2008) teacher races game has several benefits.First by doing this game, it is also teaches the pupilshow to work cooperatively in a group is. They will learnabout time management, divide job and takeresponsibility in their own group. Second, in conductingthis game, the kinesthetic activity is very dominant. Sothey will not get bored while they are learning.The researcher formulates the researchquestion as follow: (1) How is the implementation ofTeacher Races game to teach speaking of descriptivetext to the seventh grade students of SMPMuhammadiyah 2 taman? (2) How is the students ‟speaking ability toward the implementation of TeacherRaces game?Literature ReviewSpeakingNunan (2003:48) point out that speaking is aproductive oral skill in which consisted of constructingsystematic verbal, utterances to convey meaning.Meanwhile, Chaney (1998:13) describes speaking as “theprocess of building and sharing meaning through the useof verbal and non verbal symbols in a variety ofcontexts”. So, speaking is an oral skill which uses verbaland non verbal systematic symbols .Speaking is one of the important aspects in theprocess of learning language. The teacher should beaware of their students‟ speaking ability because the mainpurpose of learning foreign language is to make thestudents able to communicate. According to Nunan(2001: 39) “speaking is the single most important aspectof learning foreign language“Lado (1961: 240-241) states that speakingability is someone‟s ability to transfer their knowledgeand to express their idea in real communication byselecting correct words and systematized idea. It meansthat speaking ability is the ability to express oneself inone live situation in precise words, or the ability toconverse, or to express a sequence of ideas fluently.Teaching SpeakingThe main purpose of teaching and learningforeign language is to make the students able tocommunicate using the target language. The opportunityto speak in a group should be given to the students asmuch as possible in order to facilitate the students inusing the target language. Nunan (2001: 51) states thatlearning to speak in a foreign language will be facilitatedwhen learners are actively engaged in attempting tocommunicate.Teaching speaking must be done based on thestudent‟s level. In the speaking there are three levels ofthe students such as beginning level learners,intermediate level learners, and advanced level learners.Actually the seventh grade students of SMPMuhammadiyah is still in the beginning level learners.There are some principles for teaching speaking tobeginning level based on Bailey and Nunan (2005: 36-40) :1. Provides something for learners to talk about.2. Create opportunities for students to interact byusing group work or pair work.3. Manipulate physical arrangements to promotespeaking practice.Classroom Speaking ActivitiesThere are many speaking activities that can bedone in the classroom during the teaching and learningprocess. According to Harmer that there are some of theThe Use of Teacher Races Game in Teaching Speaking Descriptive Text3speaking activities that widely-used in the classroom(2002: 271-275): Acting from a Script Communication games Discussion Prepared Talks Questionnaire Simulation and role play The roles of the teacherDescriptive TextDescriptive text ix one of the text-genres whichshould be taught in secondary school, they are junior andsenior high school. Depdiknas (2003:49) definedescriptive text as a text which is used to describe aparticular person, place or things. Descriptive text isdifferent from report text because it describes a specificsubject rather than a general class.Depdiknas has also classified the characteristicsmust have been different from other text-genres. Here,Depdiknas differ them into several points:1. Social FunctionBased on depdiknas (2003:49), descriptive text has asocial function describe a particular person, place,or things. It means that, by learning descriptive text,the students are supposed to be able to describe thephysical appearance and the personality of aparticular person, or even the physical appearance,the characteristics, and the quality of a certainplace.2. Generic StructureAccording to Depdiknas (2004:52), the schematicstructures in generic structure of descriptive textare: Identification : in this part, we describe thephenomenon that we have in mind. Description : after expressing the main point inidentification, we will explain it more in supportingdetail to give clearer description of particular parts,qualities, and characteristic. Since the study focuseson describing people, the identification will be onthe people, the identification will be on the peoplethat are going to described.3. Linguistic FeatureThe linguistic features of descriptive text are dividedinto several points as follows: certain nouns,detailed noun phrases, adjective, verb, figurativelanguage to describe something in more detail,simple present tense.GameGibbs (1978:60) states that a game is an activitycarried out by cooperating of competing decision makers,seeking, and active. Within a set of rules and theirobjectives, games are closed activities, in other words,they have a very clearly mastered.Game is an activity that could give enjoyment inteaching and learning process between the teacher andthe students. It is also such a great way to encourage thewhole students in the class to work together and toprovide an often-welcome change in working pattern.They are mostly applied to young learners.Teacher Races GameTeacher races game is one of the game which iscommonly used in some language courses. In this game,the students will work in group of five to six, but eachmember of the group have own task. Each member has toanswer the question that have been given before to theteacher. The teacher is waiting outside the classroom.While approaching to the teacher, the delegation is notallowed to bring out the paper. They must memorize theanswer. The teacher decide whether the students get thepoint or not based on the accuracy and fluency thestudents‟ answer. If the answer is not proper yet, theteacher will say “sorry, your answer is not proper yet, goback and repair your answer”. However if the answer isproper, the teacher will give a sign.To obtain the goal of the study, the teachershould decide to use the appropriate media in teachinglearning. There are many kinds of media, one of them ispicture. Pictures are appropriate media to be used inteaching learning process, especially in teachingspeaking. Individual picture also can be used as a mediain “Teacher Races” game. The students will not getdifficulties to describe a particular thing by usingindividual picture. According to Sadiman et,al, (1993:29)among teaching, pictures are commonly used as visualmedia. In this case, pictures can help students to visualizelanguage from abstract to concrete.Besides that, pictures can give stimulus for thestudents to be more creative and attract the students tospeak. On the other hand, pictures are the most availableteaching material (Yunus1981:50). Pictures that are usedas the media in teaching learning process can be obtainedeasily. Because pictures are simple, cheap, and everyonedoes not nedd much money to get it. The teachers can cutpictures from books, magazines, newspaper, and they cancopy it from flashdisk, etc. therefore, pictures are aninteresting media which can be used in the learningprocess.The Rules of Teacher Races game1. Ask the students to make a group of seven. Onegroup consist of six students. Then explain that eachmember have own task.Ejournal Unesa. Volume 01 Nomor 01 Tahun 2013, 1 - 112. Choose a proper picture which is suitable with thetopic. The picture must be clear enough.3. Give the different picture all of members.4. Explain that each member must send theirdescriptive monologue to the teacher.5. The teacher wait outside the classroom.6. After the students receive their picture. Then theyhave to deliver their description to their teacher oneby one.7. Teacher decide whether the answer proper or not.Proper means they can describe about the picture thathave been given.8. If the description is proper enough. teacher will givesign equal with one point.9. The winner group is the fastest group that have moresign.The Benefit of Teacher Races GameTeacher races game has many benefits for thestudents, by doing this game, the motoric aspect isexplored, by doing motoric activity, the students will notget bored. Smith (2008) states that teacher races game isnot difficult to prepare and not spending so much money.Smith (2008) also states that teacher races gamehas several benefits. First by doing this game, it is alsoteaches the pupils how to work cooperatively in a groupis. They will learn about time management, divide joband take responsibility in their own group. Second, inconducting this game, the kinesthetic activity is verydominant. So they will not get bored while they arelearning.The Implementation of Teacher Races Game inTeaching Speaking of descriptive text.The illustration below showed the steps of theteaching speaking descriptive text using teacher racesgame.Pre ActivityIn pre activity, the teacher told the students aboutthe objective of study that they will learn. The teacherexplains about a descriptive text included the genericstructure and the language features. The teacher teachesthe vocabulary about the parts of the person. Then theteacher ask one students to come in front of class as amodel as the example. The teacher asked to the studentswhat the friend is and ask the students to describe it.For example: The teacher ask Muhammad fikri to comein front of class, Then, the teacher let the studentsdescribes Muhammad fikri is. If the students getdifficulties in understanding the teacher‟s oral descriptivemonologue, they may open their dictionary to find out thevocabularies they don‟t understand its meaning. Afterthey successfully describe the person correctly, theteacher will give them appreciation by making applausetogether which indirectly aims to make the students moreattracted and interested to join the game.Whilst ActivityAfter the students really understand about theexplanation before, the next is the teacher has to prepareeverything that related to the material which is used toconduct the teacher races game. In this case, the teacherprepare the person picture. Then he asked the students tomake a group pf six. The number of the students in SMPMuhammadiyah is 42 students, means every group have7 members. After that, the teacher distribute a picture toevery member, then he explain about what the studentswill do in teacher races game, the goal, rules, and also thereward that they will get if become the winner, this is tomotivate the students to be more active in learningactivity.In this step, time to play teacher races game.This game can be played for 30 minutes. They work ingroup but their send their own task that is describing apicture to their teacher individually, the teacher waitoutside the class. He waits the description of eachmember of group who are ready to give description.Post ActivityThe students who already send their descriptionto the teacher will get sign, one sign equal one point. thissection will make some noisy since all ofmember/students are hurry to give their descriptivemonologue to the teacher. However, through this activity,most of students focus on the lesson more than if weteach them by conventional way. For the last doing thisgame. (in last meeting), the students had to send theirdescriptive monologue in front of class. To make themmore briefly to speak. Then The fastest group who havemore sign is the winner. So, teacher will give reward tomake them more active.Review of Previous StudyThe researcher found a previous study which hassimilarity with this study. The previous study is “TheEffectiveness of Using Teacher Races Game to TeachSimple Past Tense in Recount Text for Eight Graders ofSMP Negeri 13 Surabaya.” which was conducted byRatna Ayu Pawestri Kusuma Dewi (2012). It was anexperimental research that focused on the teaching ofsimple past tense in the recount text. she didn‟t used amedia in that game, she only gave some question to thestudents and the students had to answer the question.The study is conducted by the researcher withdifferent media from the one in the previous study, thisstudy use person pictures. The researcher applied picturesmedia in Teacher Races gameThe Use of Teacher Races Game in Teaching Speaking Descriptive Text5RESEARCH METHODOLOGYThis chapter describes the steps taken to conductthe study. The description involves research design,subject, setting, data of the study, data collectiontechnique, and data analysis.This study used a descriptive qualitative research.The subject of this study were the teacher and the aeventhgraders of SMP Muhammadiyah 2 Taman. The setting ofthe study was Muhammadiyah 2 Taman which is locatedon Wonocolo jl. Belakang pasar lama sepanjang. Theresearcher collected the data through some instruments.The instruments were observation checklist and students‟speaking rubric performance from Haris‟s rubric ofspeaking proficiency. The first data was observationresult which was taken from observation checklist. Thesecond data was the result of the students‟ speaking scorewhich was taken from students‟ speaking rubricperformance.RESULT AND DISCUSSIONThis chapter contains the description of the data obtained.The researcher will describe the data from the dailyobservation and assessment which show the condition ofthe class and the students‟ speaking ability during theimplementation of Teacher Races game. The dataobtained from the observation checklist and the students‟speech were analyzed based on the criteria of each aspectin the Hari‟s speaking proficiency measurement.ResultsThe research was conducted in three meetings.Here, the researcher described the results based on theobservation checklist and students‟ speaking score. Theresearcher divided the results into two chapters. The firstchapter described the implementation of Teacher Racesgame to teach speaking of descriptive text to the seventhgrade students of SMP Muhammadiyah 2 Taman. Thesecond chapter described the students‟ speaking abilitytoward the implementation of Teacher Races game.The Observation Results of Teacher Races Game ActivityDuring the research, the observation wasconducted by the researcher through data observationchecklist. The researcher observed directly while theteacher was implementing Teacher Races game. Theobservation was done in three meetings.1. The First MeetingThe first meeting was held on Monday, 6th 2013. Thetime was 2x40 minutes. Before starting the lesson, thefirst thing that the researcher did was greeted the studentsand introduced the researcher to his students.Then hechecked the attendance list before starting the lesson. Hecalled every name of class 7-A students and threestudents were absent today. Then the teacher explainedthe objectives of the study at that day. At that time theteacher reviewed the material of the descriptive textbecause he had taught the descriptive text last week.After that he gave vocabulary list related to thedescribing person to the teacher.Then the teacher continued the explanation about thelanguage feature about descriptive text. After that, theteacher let the students to made pairs. There were somestudent complaining about the teammates. She didn‟t getthe partner. Then the teacher divides students by theabsent number.The teacher introduced the rules, the topic, andlanguage features related to Teacher Races Game. Healso influenced and encouraged the students to becreative and free to speak. Before starting the game, shechecked students‟ understanding by giving theopportunity to ask some questions related to the game.First of all, the teacher asked one students to came infront of class as a model as the example, there wasMuhammad Fikri. The teacher asked to the students whatthe Muhammad fikri was and asked the students todescribe it. If the students got difficulties inunderstanding the teacher‟s oral descriptive monologue,they might opened their dictionary to find out thevocabularies they don‟t understood its meaning. Afterthey successfully describe the person correctly, theteacher gave them appreciation by making applausetogether which indirectly aims to made the students moreattracted and interested to joined the game.After gave the example, the teacher asked thestudents to make groups of seven. Each group consistedof six students. Then, the teacher distributed a picture toevery member of the group. There were famous person atthe first meeting. After getting the picture, all of themember of the groups had time to made description aboutthe picture which they had got. The group did not take along time. It seemed that the students in the class wereaccustomed to work in group.The teacher gave 15 minutes to the students todiscuss the picture and to gain the information about theperson. During the discussion, the teacher was goingaround the class to checked and to helped the studentswhether they had difficulties or not.After that, the teacher wait outside, then the studentshad to sent their description to the teacher individually.The students who already sent their descriptionmonologue to the teacher get a sign equal one point. Thesign was a smile emoticon. The fastest group and gotmore sign is the winner.The teacher listened and paid attention to thestudents‟ performance, the teacher corrected severalEjournal Unesa. Volume 01 Nomor 01 Tahun 2013, 1 - 11students‟ mistakes such as mispronunciations,grammatical errors, wrong choice vocabularies, improperfluency and comprehension.In the end of the game, group C was the winner.After conducting the game, the teacher appreciated thestudents by giving applause. Though there were manymistakes done during the speaking activity, it did notmake students gave up. Then, the teacher correctedpronunciation errors, sentence constructions, and the useof the language, after that the teacher asked the studentsto brought a picture of their father/mother for the nextmeeting.The students were enthusiastic with the game, Whilethe teacher was teaching implementing teacher racesgame, the observer observed all activities that happenedwhether it harmonized with all aspects stated in the fieldnote well or not. The observation process included thepreparation, the presentation, the technique or method andthe students- teacher interaction2. The Second MeetingThe second observation was held on May, 7th, 2013,at that time, the class began at 07.00 a.m. and ended at08.30 a.m. the teacher entered the class and greeted thestudentsBefore the teacher began the learning activities, hechecked the attendance list. There were thirty eightstudents who joined the class. There were three studentswho was absent. Then the teacher began the learningactivity and started with the objective of the study at thatday that was implementing of teacher races game inspeaking of descriptive text.As a warming up activity, the teacher gave theexample by described about his father. In the mainactivity, the teacher introduced the game that would beplayed. The game and its rules were the same but useddifferent object. The object had to described was thepicture that have been brought by the students. There wasthe picture of the students‟ parents.The teacher gave 15 minutes to the students todiscussed the picture and to gain the information aboutthe person. During the discussion, the teacher was goingaround the class to check and to help the studentswhether they had difficulties or not.After that, the teacher wait outside, then the studentshad to send their description to the teacher individually.The students who already sent their descriptionmonologue to the teacher get a sign equal one point. Thesign was a smile emoticon. The fastest group and gotmore sign is the winner.The teacher listened and paid attention to thestudents‟ performance, the teacher corrected severalstudents‟ mistakes such as. In this second observation,the students‟ performance was better than in the firstobservation.Based on the observation, it could be said that theteaching learning process was successfully done. Theteacher felt happy with the improvement made by thestudents in this meeting. The class became very activeand alive. All students tried to speak up and some ofthem asked some questions to the teacher. The topic andalso the technique of the teacher was able to motivate thestudents. The students‟ speaking ability was getting betterthan in the previous day.After that the teacher gave the conclusion of thelesson today. The last the teacher said goodbye and leftthe class.The Third ObservationThe third observation was conducted on May 13th,2013. This was the last day of the implementing TeacherRaces Game. There were only 38 students because 2students were absent. The teacher started to begin thelesson with opening session. The teacher greeted andasked the students the previous lesson that they hadstudied. It was meant to know whether or not they stillremember about the previous lesson. Then she checkedthe attendance list. Then he began the activities/the game.In the third meeting, the game was different. In thatmeeting, the teacher asked the students to make presentthe descriptive monologue about their best friends infront of class without any preparation. The teacher onlygave 5 minutes to the students to prepare their descriptivemonologue. Then the students had to describe their bestfriend in front of class. The student who had already senttheir description got a sign equal one point. The fastestgroup and had more sign is the winnerWhile the students were working their task, theteacher controlled the class by monitoring the students‟behavior. He walked around the class and helped thestudents who got difficulties in working their task. After15 minutes was over, the students have to came to theteacher and send their description. The fastest group whohad more sign is the winner.In the end of the game, group C was the winneragain. Because that was the last conducting this game.The researcher gave a reward to the winner group andalso to all of students in that class. And also, the teacherappreciated the students by giving applause. Thoughthere were many mistakes done during the speakingactivity, it did not make students gave up. Then theteacher corrected mispronunciations, grammatical errors,wrong choice vocabularies, improper fluency andcomprehension.The Use of Teacher Races Game in Teaching Speaking Descriptive Text7The Result of the Students’ Speaking Ability ofDescriptive Text by Using Teacher Races Game.To answer the second question of the researchquestions, the researcher scored the students‟performance by using rubric from Haris (see appendix).There were five components that were measured such asthe students‟ They are pronunciation, grammar,vocabulary, fluency, and comprehension. Everycomponent has been analyzed based on the criteria in therubric for descriptive text.The First MeetingThe first meeting was on May 7th 2013. Based on thestudents‟ performance, mostly they were able to speakEnglish.The first descriptive speaking task was given to thestudents at the first meeting. The students were asked tomake a group, then they have to describe about certainperson individually.The following description are the result of students‟speaking ability in the first meeting. The researcher took4 students as the examples of the progress in the speakingability. Those 4 students were student A, student B,student C, and student D. Here is the result of descriptivemonologue by student A,B,C, and D1. Student A : Varin (student number 37 in 7A)“Hallo, my name is Varin. I want describeObama. He is the president of United State ofAmerica. He Is handsome, he has sharp nose, curlyhair, but he has brown skin. Obama was live inIndonesia.At the first meeting, Varin was in the second level ofpronunciation. She always repeat her words and not clearin pronounced the words. For the grammar aspect shefrequent errors of grammar which didn‟t obscuremeaning. She used limited vocabulary to describe theperson. Then, in fluency aspect, her speech was veryslow and uneven except for short or routine sentence. Inthe comprehension aspect, she was in the second level,she understand only slow and requires constantrepetition, in explaining the language feature and genericstructure of descriptive text.2. Student B : Syailendra (student number 21 in 7-A)“Hai..my name is Rico. I want describe Lunamaya. His nose is sharp, skin is white, he is tall,and beautiful. He has many friends because heis beautiful girl. His favorit hobby is singing.”In the first meeting, Student B‟s pronunciation wasin the second level, her pronunciation was very hard tounderstand. Then, in the grammatical aspect, hisgrammar was in the first level, because he used the wronggrammatical aspect. In the vocabulary aspect, his wordchoices were inadequate for even the simplestdescription. In the fluency aspect, his speech was oftenstop because of his anxiety to speak. In thecomprehension aspect, he had low understanding. Heunderstood for only the simplest description.3. Student C : Nindita (student number 24 in 7-A)“Hii… my name is Nanda. I will describe NikitaWilly. She is famous artist in Indonesia. she iscute, she has white skin, strong hair and curlyhair, she also has sharp nose, but she is not tall.She is kind girl.”In the fisrt meeting, student C was in the third levelof pronunciation, She gave the detail description aboutthe person. She used many variety vocabularies todescribe the person. Her fluency and grammar level werein third level because she spoke in speed and fluency wasrather strongly affected by language problem and . In thecomprehension aspect, she was in the Third level, sheunderstand most of what is said at slower-than-normalspeed with repetitions.4. Student D : Reina (student number 29 in 7-A)“Hallo, my name is Reina. I want to describeabout Robert Pattinson. He is the actor ofTwilight movie. He Is handsome, he has sharpnose, straight hair, and he has white skin.Every girl in this world love him. Because he ishandsome.”In the first meeting, Student D was in the second level ofpronunciation. Her pronounced was very hard tounderstand, but she gave the detail description about acertain person. Her fluency and grammar level were inthe third level because she spoke in speed and fluencywhich was rather strongly affected by language problemand she could apply the rules of simple present tenseappropriately although she made a few mistakes. In thecomprehension aspect, she was in the second level, sheunderstand only slow and requires constant repetition, inexplaining the language feature and generic structure ofdescriptive text.The Second MeetingThe second meeting was on April 11th 2013. Theresult in the second meeting was almost the same as thefirst meeting. Based on the students‟ performance, mostlythey were able to make description monologue related tothe picture. The picture on the second meeting was thepicture of their mother/father. There was animprovement. Their confidence was getting better.There was an improvement in the second meeting.The students‟ speaking ability had risen. Here, theEjournal Unesa. Volume 01 Nomor 01 Tahun 2013, 1 - 11researcher described the increasing score of student A,student B, student C, and student D, as the examples.1. Student A : Varin (student number 37 in 7A)“Hi.. Today I want to describe about my mother, thename is Mahmudah. She is 40 years old. She ishousewife. She is beautiful, she has sharp nose,she has white skin, the hair is long and straight.But she wear jilbab. I love my mother.”In the second meeting, the student A showed herprogress. she is in the third level of pronunciation, shegave clear description. Because she have good motivationin speaking English. She used rich variety ofvocabularies. Their speech was effortless and smooth. Heappeared to understand everything without difficulty. Butshe still made word-order error which did not obscuremeaning. In the comprehension aspect, she was in theThird level, she understand most of what is said atslower-than-normal speed with repetitions.2. Student B : Syailendra (student number 21 in 7-A)“Hi.. I am Syailendra, I want to describe about mymother. Name is Bu Wanda. She has straighthair, her nose is snub nose, she has whitesetengah brown skin. She is tall. Because mymother dulunya model. My mother is beautifulwoman. Thank you.”In the second meeting, Student B‟s pronunciationwas the same in the first meeting. His pronunciation washard to understand. Then, in the grammatical aspect hadraisen. In the first meeting he in the first level. But in thesecond meeting, he is the second level, he use correctgrammatical order. He use correct pronoun. In thevocabulary aspect, he use limited vocabulary. In thefluency aspect, his speech was frequently hesitant, oftenforced into silence by language problem. In thecomprehension aspect, he had low understanding. Heunderstood for only the simplest description.3. Student C : Nindita (student number 24 in 7-A)“Hi,,, Meet again with me ya sir..heheehe… Iam Nindita, I want to describe about my father.He is 40 years old. He is tall, he has beard andmustache, but no like pak raden. Hehe.. myfather has brown skin. He hobby is singing. Hehas good voice. Oke that’s all.”Student C‟s pronunciation in the second meeting wasstill the same as in the first meeting. Then, her ability inthe grammatical rules had risen. She spoke withoccasional errors that showed imperfect control of somepatterns but no weakness that caused misunderstanding.In the vocabulary aspect, she already had better choicesof word. In the fluency aspect, her speech wasoccasionally hesitant. She started to be confident whileshe were speaking. In the comprehension aspect, shequite well understood more complex speech directed toher.4. Student D : Reina (student number 29 in 7-A)“Hi.. I want to describe about my mother. Shehas straight hair, she has snub nose, she hasbrown skin, she is not tall. She is thin. She weara veil. My mother is Muslim woman. Her hobbyIs planting flower. So I have so many flower inmy house.”Student D‟s speaking ability in the second meetingshowed the same result as the first meeting. There was noimprovement in his speaking. His pronunciation wasfrequently be asked to repeat. It was hard to understand.Then, in grammatical aspect, his grammar was almostentirely inaccurate except in typical or usual phrases. Inthe vocabulary aspect, his choices of word wereinadequate for even the simplest conversation. In thefluency aspect, his speech was often left uncompletedbecause he was worried to speak. In the comprehensionaspect, he had low understanding. He understood for onlythe simplest type of description.Third meetingThe third meeting was on May 13th 2013. In thirdmeeting, students‟ speaking ability was significant better.All students mostly had better improvement than before.The following descriptions are the improving ability fromstudent A, student B, student C, and student D.1. Student A : Varin (student number 37 in 7A)“Hi.. let me introduce myself.. my name isVarin, I have best friend, the name is Tasya .She is my friend in this class. Tasya has shortand straight hair, she has sharp nose, her skin iswhite, she is not tall not short. and she is thin.her favorite food is pizza.In the third meeting, the student A showed herprogress. She was in the third level in pronunciation. Shegave enough detail description about the person. She usedan adequate variety of words and most of them werecorrectly used. Her grammar level was in third level,there were a few errors in the use of verb. Her fluencywas in the fourth level because her speed or speechseemed to be slightly affected by language problem. Inthe comprehension aspect, she was in the Third level, sheunderstand most of what is said at slower-than-normalspeed with repetitions.2. Student B : Syailendra (student number 21 in 7-A)“Assalamualaikum wr wb. My name isSyailendra. I will introduce about my bestfriend. He is Doni. He is my family. Sepupu.Hehe. He is handsome, he is tall and slim. HeThe Use of Teacher Races Game in Teaching Speaking Descriptive Text9has sharp nose, curly hair, and her skin is agakwhite. His hobby is play computer. He is smartwith computer”The pronunciation of the student number 3 was inthe second level. His pronunciation frequently asked torepeat. But he made good word-order and did not obscurethe meaning at all. he also used variety vocabularies.From the fluency aspect, her speed or speech seemed tobe slightly affected by language problems. She could giveenough clear description about the person even though hemade a few mistakes. In the comprehension aspect, shewas in the Third level, she understand most of what issaid at slower-than-normal speed with repetitions.3. Student C: Nindita (student number 24 in 7-A)“Assalamualaikum wr wb. My name is Nindita. I willintroduce about my best friend, her name isYasmin. She is beautiful, because she has sharpnose, theher hair is strong and curly hair, herhobby is eating, but she is not fat. She istalkative girl, but she is cute. That’s all Thankyou.”The pronunciation of the student C was intelligible,conscious a definite accent. She made good word-orderand did not obscure the meaning at all. She also usedvariety vocabularies. From the fluency aspect, her speedor speech seemed to be slightly affected by languageproblems. She could give enough clear description aboutthe person4. Student D: Reina (student number 29 in 7-A)Assalamualaikum wr wb.. hallo my name isReina. I want to describe about my best friend.She is my friend in this class. Her name isnabila. She has beautiful face. She has sharpnose, strong hair, and white skin.The pronunciation of the student number 3 wasintelligible, conscious a definite accent. She made goodword-order and did not obscure the meaning at all. Shealso used variety vocabularies. From the fluency aspect,her speed or speech seemed to be slightly affected bylanguage problems. She could give enough cleardescription about the person. In the comprehensionaspect, she quite understood in simple descriptionfollowed by some repetitions.DISCUSSIONIn this section, the researcher discussed two aspects.Firstly. The researcher would discuss the suitability of theimplementation Teacher Races game with the theory.Secondly, the researcher would discuss the result ofstudents‟ speaking abilityThe first thing that should be noted was thesuitability of the implementation Teacher Races gamewith the theory. Based on the observations, what theteacher had done followed the theory. Teacher Racesgame which was introduced by Smith (2002) inpracticing this game the pupils will need extra energy torun more and more to get the right answer. The activity inteacher races game and how to send their description totheir teacher can motivate the students to speak more andincrease their speaking ability. On the other hand, inconducting this game, the kinesthetic activity is verydominant. So they will not get bored while they arelearning.Teacher Races game which teacher had implementedalso followed the theory of game. A game, as it is definedby Hadfield (1984) as quoted in Ninaber (2004:10), is anactivity with rules, a goal, and element of fun. There weresome reasons why Teacher Races game was appropriate.First, From the observation, the researcher can say thatthe topics were appropriate with the students‟ interest.Moreover, the topics dealt with the local curriculumstated in the topics of the seventh grade students in thesecond semester. They were describing about person,place, noun, and others. It means that the topics stated inthe first to the third meeting were appropriate with thelocal curriculum. As a result, the study gave somecontributions for the students‟ competence.At the first meeting, it can be seen that there weremany things that should be evaluated. Some students stillgot confused with the technique. Even though thestudents found some difficulties during the lesson, thestudents felt difficult in describing person. In addition,the media were suitable with the topic. The topic couldmotivate the students because it was familiar with theirdaily life. But in the second and third performance, theylooked more confident in expressing their ideas becausethe teacher gave them support to be more confident inperformed their idea.In the first meeting, The teacher explained aboutdescriptive text, then he asked the students to madegroups and introduced about teacher races game. In thefirst meeting, the teacher asked the students to make adescriptive monologue based on the picture that havebeen given by the teacher. The students sent theirdescription to their teacher individually. In the secondmeeting, the students produced descriptive monologuebased on the picture of their own parents. The teachermade it different because it could make them not to bebored because of the same topic as the last meeting. Inthis activity, the teacher asked the students to performedspontaneously. In the third meeting, the teacher asked thestudents to make a descriptive monologue about theirbest friend. Because this is the last meeting, the studentsdid not permitted to bring a picture. From thisperformance, the students did better than before. BecauseEjournal Unesa. Volume 01 Nomor 01 Tahun 2013, 1 - 11from this performance, who got better performance, got areward.The second was the results of students‟ speakingability. The students‟ speaking ability was getting betterfrom the first meeting until the third meeting. Thestudents had practiced speaking more than before.There were five components; pronunciation,grammar, vocabulary, fluency, and comprehension hadbeen analyzed. Most of them made a progress in eachcomponent. Based on the observation of the studentsperformance, at the first meeting of using Teacher Racesgame in the teaching learning process of speaking, mostof students only could performed simplest describingperson . They were reluctant to deliver their idea. Thepronunciation frequently was hard to understand. Thecomprehension was quite good with the occasional errorson grammar. In the second meeting, there was a littlesignificant improvement to their speaking ability. Theycould relax in performing their idea. The pronunciationhad been corrected. There were still errors on grammarbut not as much as in the first meeting. The students‟understanding was also good. In the third meeting, therewere some changes in the students' speaking ability. Inthis meeting, most students could speak confidentlythough there were still errors on grammar. Thepronunciation was better than the previous day. Thefluency and the comprehension were better than thesecond day. The students were more familiar withEnglish better than two previous days.From the above explanation, it could be concludedthat there was an increase in the students' speaking abilitytaught by Teacher Races games in the process ofteaching-learning. The students‟ speaking ability wasgetting better in every meeting and it can be seen fromthe scores of the students' speaking descriptive task. Thetable showed that the scores of the students were gettingbetter. Some students got bad marks in the first and twomeeting, and finally achieved better in the last meeting.By looking at the result of students speaking descriptivetask, the researcher concluded that the technique couldhelp the students in their understanding.From the observation, the researcher can say thatTeacher Races games helped to motivate the students andreduced their boredom in the learning process. TeacherRaces Game became better technique that fulfilled thestudents' interest in the learning process. Thus, it could beconcluded that Teacher Races game has manycontributions to the teaching of Speaking of Descriptivetext.ConclusionTeacher Races game can be applied as a technique toteach speaking because this technique is able to increasethe students‟ interest to speak up in the speaking class. Atthe beginning of the lesson, the teacher explain aboutdescriptive text, then did a game. In addition, theapplication of Teacher Races game helped the students tomemorize the vocabulary easily and it could reduce thestudents‟ boredom so they could participate actively inthe learning process.Suggestion1. Teacher Races game can be applied to teachspeaking of Descriptive Text to the seventhgraders of junior high school in order to buildstudents‟ willingness to speak up and to makestudents interest in English language.2. The teacher should prepare an interesting mediato reach the goal of teaching learning process,because an interesting media will lead thestudents to be more enthusiastic to3. The material should not too easy or too difficult.It must be in accordance with the students‟ability.REFERENCESAllen, D.E and Vallete, RM. 1997. ClasroomTechniques: Foreign Languagesand English as Second Language. New york:Horcourt Grace Jovanovich, Inc.Byrne, Donn. 1976. Teaching oral English. Hongkong:LongmanBrown. 2001. Teaching by Principles. San FransiscoState University .LongmanBrown, H Douglas. 2004. Language AssessmentPrinciples and ClassroomPractice. USA: Pearson Education, Inc.Departemen Pendidikan Nasional. 2006. Standar Isi danStandar KompetensiKelulusan: Mata Pelajaran Bahasa Inggris.Jakarta: Depdiknas.Delliyana, N. 2008. The Teaching of Grammar in AnInternationalStandardized School. Unpublished S-1 Thesis.Surabaya: SurabayaState University.Dewi, Ratna Ayu. 2008. The effectiveness of TeacherRaces Game to TeachThe Use of Teacher Races Game in Teaching Speaking Descriptive Text11Simple Past Tense in Recount Text for EightGraders of SMP Negeri 13Surabaya. Unpublished S-1 Thesis. Surabaya:Surabaya State UniversityHalfield,J. 2005. Intermediate Writing CommunicationGames. England:LongmanHarmer, Jeremy. 2001. The practice of English languageTeaching. England:Longman.Harmer, Jeremy. 2002. The practice of English languageteaching. New york:LongmanHarmer, Jeremy. 2003. The Practice of English LanguageTeaching. England:Longman.Harris, David P. 1969. Testing English as a secondlanguage. New York: MCGraw HillIskandar. 2009. Psikologi Pendidikan Sebuah OrrientasiBaru. Ciputat: GaungPersada PressLado, Robert. 1964. Language teaching: A scientificapproach. Bombay: MCgraw-Hill publishing.Nunan, david. 2001. Language teaching methodology.London: Prentice hallinternational.Nunan, David ed. 2003. Pratical English LanguageTeaching, First editionSingapore: Mc Graw Hill.Nunan, david. 2005. Practicing English languageteaching grammar.New york: Mc Graw-Hill ESLPyles, Thomas and john, Algeo.1968.English anIntroduction to language.USA:Harcourt Brave Jovanovich, Inc.Sadiman, Arief S, R. Raharjo, Anung H aryono, andRahardjo, 1993. MediaPendidikan: Pengertian, Pengembangan, dan,Pemanfaatannya,Jakarta: PT. Raja Grafindo Perkasa.Smith, Helen. 2008. British Council „Running Dictation‟.It is Retrieved from(http://www.Britishcouncil.org/flashonlinelessons-all-ages-running-dictation.doc)